Effects of high-intensity interval cycling performed after resistance training on muscle strength and hypertrophy - Tsitkanou, S.; Spengos, K.; Stasinaki, A.-N.; Zaras, N.; Bogdanis, G.; Papadimas, G.; Terzis, G. (Scandinavian Journal of Medicine & Science in Sports, 2017)
Aim of the study was to investigate whether high-intensity interval cycling performed immediately after resistance training would inhibit muscle strength increase and hypertrophy expected from resistance training per se. Twenty-two young men were assigned into either resistance training (RE; N = 11) or resistance training plus high-intensity interval cycling (REC; N = 11). Lower body muscle strength and rate of force development (RFD), quadriceps cross-sectional area (CSA) and vastus lateralis muscle architecture, muscle fiber type composition and capillarization, and estimated aerobic capacity were evaluated before and after 8 weeks of training (2 times per week). Muscle strength and quadriceps CSA were significantly and similarly increased after both interventions. Fiber CSA increased significantly and similarly after both RE (type I: 13.6 ± 3.7%, type IIA: 17.6 ± 4.4%, type IIX: 23.2 ± 5.7%, P < 0.05) and REC (type I: 10.0 ± 2.7%, type IIA: 14.8 ± 4.3% type IIX: 20.8 ± 6.0%, P < 0.05). In contrast, RFD decreased and fascicle angle increased (P < 0.05) only after REC. Capillary density and estimated aerobic capacity increased (P < 0.05) only after REC. These results suggest that high-intensity interval cycling performed after heavy-resistance exercise may not inhibit resistance exercise-induced muscle strength/hypertrophy after 2 months of training, while it prompts aerobic capacity and muscle capillarization. The addition of high-intensity cycling after heavy-resistance exercise may decrease RFD partly due to muscle architectural changes.